ANALISIS LAYANAN FINANCIAL TECHNOLOGY DAN GAYA HIDUP TERHADAP PERILAKU KEUANGAN MAHASISWA - Aditya Ferdiansyah; Nunuk Triwahyuningtyas (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
This research is a quantitative research. The purpose of this study was to  determine the relationship between the influence of financial technology services  variables and lifestyle on student financial behavior variables. The Veterans  National Development University Jakarta is the place to do research by taking the  student population of the Faculty of Economics and Business. The number of  samples used was 360 students who were obtained using the Slovin formula.  Probability sampling with simple random sampling technique was used as the  sampling method in this study and Partial Least Square (PLS) was used as the  analysis technique. This study shows that financial technology services have a  positive and significant effect on student financial behavior. This shows that the  higher the use and benefits of financial technology services, the better the  student's financial behavior will be. The results of lifestyle variables also show a  positive and significant effect. So the conclusion for lifestyle variables is that even  though students of the Faculty of Economics and Business, Universitas  Pembangunan Nasional Veteran Jakarta have a trendy and modern lifestyle, they  are able to manage their finances well.